Migration, Fake News and Communication Conflicts: A Study about Syrian Immigrants in Turkey - Haya Androon Hafez,; Recep Ünal, (Communication Today, 2025)
As a result of the conflict in Syria in 2011, approximately 3.5 million Syrians migrated to Turkey. A significant number of news articles about Syrian refugees have been produced in traditional media, and various types of content have been created on social media. However, some of these news stories and posts have been based on inaccurate information. This research aims to examine how Syrian refugees interpret the fake news spread about them and how such content affects their daily lives and their relationships with Turkish society. To achieve this objective, focus group discussions were conducted with Syrian refugees working in civil society centres. Various questions were posed to the Syrian refugees about the impact of the spread of fake news on their daily lives, how such news affects their communication processes within society, and what solutions they propose. During the focus group discussion, media texts were distributed which contained fake news or misinformation. According to the study’s findings, Syrian refugees frequently encounter fake news in their daily lives, and these reports have negative effects on their daily lives and their integration into the social life of which they are part.